HUBUNGAN ADIKSI GAME ONLINE DENGAN KERENTANAN STRES PADA SISWA SMAN 15 PADANG - Henry Judana Simbolon (Jurnal Medika Hutama, 2026)
Online game addiction is a disorder involving all types of problematic online gaming activities. All of these activities stem from excessive use of internet-connected devices (i.e., computers, smartphones, and other devices for gaming and navigation). Online game addiction is influenced by certain factors, one of which is stress vulnerability. This study aims to determine the relationship between online game addiction and stress vulnerability in students of SMA Negeri 15 Padang. The type of research used is a comparative analytical categorical with categorical through a cross-sectional approach. The method of data collection is by distributing questionnaires to respondents, namely the Indonesian Online Game Addiction Questionnaire (IOGAQ) questionnaire for online game addiction and the Miller and Smith questionnaire to assess the level of stress vulnerability of respondents. The data used are primary data with a minimum number of respondents of 140 people. This study uses univariate and bivariate data analysis followed by a chi-square statistical test. The results of this study indicate a significant relationship between online game addiction and stress vulnerability in students of SMA Negeri 15 Padang with a p-value of 0.044. Respondents who were not addicted had an average of moderate stress vulnerability with a percentage of 62.16% and respondents who were addicted had an average of high stress vulnerability with a percentage of 46.67%. Therefore, it can be concluded that there is a meaningful relationship between online game addiction and stress vulnerability of students at SMA Negeri 15 Padang.